2008
DOI: 10.1074/jbc.m803234200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation of the Nonclassical Secondary Cell Wall Polysaccharide from Bacillus cereus ATCC 10987

Abstract: Nonclassical secondary cell wall polysaccharides constitute a major cell wall structure in the Bacillus cereus group of bacteria. The structure of the secondary cell wall polysaccharide from Bacillus cereus ATCC 10987, a strain that is closely related to Bacillus anthracis, was determined. This polysaccharide was released from the cell wall with aqueous hydrogen fluoride (HF) and purified by gel filtration chromatography. The purified polysaccharide, HF-PS, was characterized by glycosyl composition and linkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
1
32
1
Order By: Relevance
“…8). In their previous work, Leoff et al (23,24) did report the presence of Ne HF-PS polysaccharide in the B. cereus ATCC14579 without providing its full structure but conclusively established the fine structures of its equivalent in a wide panel of B. cereus strains (41). In contrast, these authors never mentioned the presence of an equivalent of Ch HF-PS in any B. cereus strain, including Bc 14579, or in B. anthracis (23-25, 27, 41).…”
Section: Hf-ps Consisted Of Three Monosaccharide Units (Signals I To mentioning
confidence: 99%
See 4 more Smart Citations
“…8). In their previous work, Leoff et al (23,24) did report the presence of Ne HF-PS polysaccharide in the B. cereus ATCC14579 without providing its full structure but conclusively established the fine structures of its equivalent in a wide panel of B. cereus strains (41). In contrast, these authors never mentioned the presence of an equivalent of Ch HF-PS in any B. cereus strain, including Bc 14579, or in B. anthracis (23-25, 27, 41).…”
Section: Hf-ps Consisted Of Three Monosaccharide Units (Signals I To mentioning
confidence: 99%
“…We first established that the polysaccharide fraction released by HF from B. cereus strain ATCC 14579 grown in planktonic conditions was composed of two distinct polysaccharides presenting very different structural features. Whereas one presented strong similarities with HF-released polysaccharide (HF-PS) isolated from B. cereus 10987 (24), the other one exhibited totally original structural features. Then, we demonstrated that these two polysaccharides were differentially regulated along the growth of bacteria in the biofilm phase but not in the planktonic phase.…”
mentioning
confidence: 99%
See 3 more Smart Citations